CLASSIC BOOK, IS IT STILL RELEVANT? AN IN-DEPTH STUDY OF ADABUL ALIM WAL MUTA'ALLIM CONTENT TO TEACHER AND STUDENT INTERACTIONS IN CONTEMPORARY ERA - Anis Yuni Maulida; Abd. Muqit; Wiwin Luqna Hunaida; Muhammad Fajrus Surur (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
This research is driven by the interaction between teachers and students in the contemporary era, which is associated with the content of the book Adabul Alim wal Muta'allim. For instance, the disappearance of etiquette, both between teachers and their students and vice versa. In the contemporary era, this seems to be considered irrelevant to the contents of the book Adabul Alim wal Muta'allim, possibly due to cultural influences and the surrounding environment. In this contemporary era, most teachers and students do not often study the book Adabul Alim wal Muta'allim and lack an understanding of what a teacher and a student should ideally do. This aspect is essential for researchers to investigate, aiming to understand the reasons why the interaction between teachers and students in this contemporary era is considered irrelevant to the contents of Adabul Alim wal Muta'allim. The method used is library research, collecting data in the form of documentation, such as documents from various sources like journals, theses, and websites, which are gathered and observed for careful selection. The conclusion drawn from this research is that the interaction between teachers and students in the contemporary era is not yet considered relevant to the content of Adabul Alim wal Muta'allim. This could potentially lead to further research on how the content of Adabul Alim wal Muta'allim could become relevant to education, especially in terms of teacherstudent interactions